Tuberculous Mastitis- A Outpatient department based study in Dhaka National Medical College Hospital - Jahan, Shamima; Hassan, Munir (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Tuberculous mastitis is a diagnostic dilema because of its variable presentations. Introduction: Tuberculous mastitis is a chronic granulomatous infection that affect female breast though it can affect any human organ except cardiac muscle. Material & Method: It is a retrospective study starting from July 2010 in Breast and Anal clinic to Fast track service to July 2016. This study includes 28 women (n=28) who were at direct observation & follow-up throughout the treatment period. Youngest person of this series is 20 years of age and the eldest one is 40 (Mean age-29.2). Most patients were from low economy group. The aim is to observe the diversity of presentation & management in Tuberculous mastitis. Result: Presentations are widely variable ranging from breast lump of different sizes, single or multiple breast abscess and chronic discharging sinus. 27 person have pathology in their left breast. Only one patient was diabetic. For evaluation, all routine investigation including X-ray of Dorsal spine was done but attention was given to tissue diagnosis by either Fine Needle Aspiration Cytology or Biopsy taking as Out Patient Department case for histo-pathological examination. After confirmation of diagnosis, anti-TB drug started through Directly Observed Treatment centre. Weekly follow-up was advised to those patients who needed wound care as well as daily dressing. 12 month anti-TB drug was given to all patient& all of them recovered commonly leaving behind few scars in their breast. Discussion: Extra-Pulmonary Tuberculosis is a gradually increasing chronic infectious disease in low economy patients. Limitation of this study is irregular medication and follow-up as well as drop out after starting management though Directly Observed Treatment centre is of great help. Conclusion: The entire situation may be better controlled by increasing awareness among the people and improving living standard. J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 37-39